Performance Evaluation of Different Controllers in SDN Networks - احمد احمد; ديب حازم (Latakia University Journal -Engineering Sciences Series, 2021)
Software Defined Networking (SDN) is a new networking concept and is also the most discussed topic of networking technology in recent years. This approach is also characterized by the separation of the data and control planes. The SDN proposed an approach which involves in moving the network’s intelligence out from the packet switching devices and putting it into a centralized logical controller. Controllers act as the control point for networks to manage flow between the Application layer and the Data layer through the Southbound API’s and the Northbound API’s to create a more flexible network. The forwarding decisions are primarily done in the controller and then moves down to the switches where it directly executes the logical decisions. Therefore, controllers are critical to the success of SDN networks. In this paper, the basic functions and features of SDN controllers have been discussed, also the performance of multiple controllers has been evaluated on two metrics: Throughput and Latency which had been calculated on varying network sizes by increasing the number of switches and threads in each network.